Airplane! [videorecording (DVD)] - Bernstein, Elmer (Widescreen DVD collection., 2005)
In this spoof of disaster movies, Ted Striker, an ex-Navy pilot, just got dumped by his long-time girlfriend Elaine Dickinson, who works as a stewardess. In his wish to get her back, he follows her aboard a plane, although he has had a deep aversion against anything winged since he lost several men in the war. During flight, he tries to make up with her again and again, but a crisis looms as the crew and many passengers get seriously ill due to a bad fish meal. Now, it is up to him to land the airplane safely, before the poisoning starts causing casualties. But Ted Striker's aversion to piloting is a serious psychosis, which breaks open and needs to be cured--right now.